The application of jet grouting technology to reduce ground deformation of construction the metro line in Ho Chi Minh City - Nguyen Anh Tuan, Nguyen Anh Tuan; Tran Duc Chinh, Tran Duc Chinh; Nguyen Thanh Dat, Nguyen Thanh Dat (КНУБА, 2016)
Slump and subsidence of surface deformation are concerned mostly in the process of construction of the Metro, especially in a weak soil environment, which affects the existence of buildings on the ground. This article introduces the application of Jet Grouting technology to reduce deformation of the surface when the Metro tunnel is constructed in the geological condition of the area of Ho Chi Minh City. Jet Grouting is the mixture of soil and cement (Soilcrete) created by the method of drilling the high grout pressure. Using Jet Grouting to strengthen the ground around the tunnel is seen as an effective solution to reduce surface subsidence.
Keywords: surface subsidence; drilling the high grout pressure; jet grouting; soilcrete; soilcrete; 656.4(597)